2003
DOI: 10.1016/j.cardiores.2003.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Conduction slowing by the gap junctional uncoupler carbenoxolone

Abstract: Carbenoxolone-induced uncoupling causes atrial and ventricular conduction slowing without affecting cardiac membrane currents. Activation delay is larger in poorly coupled cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 42 publications
5
60
1
Order By: Relevance
“…With the use of DT-MRI and histology, our findings on subepicardial myofiber orientation patterns are consistent with Streeter et and Bassett (52), who similarly examined this in porcine. We further demonstrated that the differential effect of RSGS on CV L vs. CV T was mediated by the distribution of GJs, known to exist predominantly at endto-end intercalated disks than side-to-side in normal hearts, by inducing cellular uncoupling (14,26). This eliminated the increase in CV L during RSGS.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…With the use of DT-MRI and histology, our findings on subepicardial myofiber orientation patterns are consistent with Streeter et and Bassett (52), who similarly examined this in porcine. We further demonstrated that the differential effect of RSGS on CV L vs. CV T was mediated by the distribution of GJs, known to exist predominantly at endto-end intercalated disks than side-to-side in normal hearts, by inducing cellular uncoupling (14,26). This eliminated the increase in CV L during RSGS.…”
Section: Discussionmentioning
confidence: 65%
“…Given the dependence of RSGS-mediated CV increase on fiber orientation (and hence GJ distribution), we examined whether the increase in CV L was mediated via GJ modulation. Cellular uncoupling was achieved with carbenoxolone (1.4 -1.6 mg/kg), a GJ blocker (14,26), resulting in complete abrogation of the CV L response to RSGS 24.7 Ϯ 8.9, Ϫ2.6 Ϯ 3.7, and Ϫ2.8 Ϯ 3.9% (P Ͻ 0.001), respectively, for control, esmolol, and carbenoxolone, respectively (Fig. 3, E and F).…”
Section: Sympathoexcitation Increases CV In Normal Ventricularmentioning
confidence: 98%
“…Carbenoxolone (CBX) is a glycyrrhetinic derivative and a putative GJ blocker. 28 When CBX was injected for 1 min following 30 min of ischemia, the LY/DR ratio was reduced from 2.5 to 1.2 in the risk area (0 min of reperfusion in Figure 6C). These results suggest that after 30 min of ischemia, GJIC increases in the risk area without membrane disruption, whereas it remains low in the non-risk area.…”
Section: Brief Ischemia Enhances Gjicmentioning
confidence: 93%
“…In this regard, CBX treatment alone has little effect on expression of proinflammatory cytokines, chemokines, or MHC molecules in BM DCs, suggesting that other molecular pathways are involved. 39 It is unlikely that the mechanism involves the potential for CBX to inhibit gap junctions, 40 because these effects would be predicted to have a negative rather than positive effect on crosspresentation. 41 However, confirmation that the positive effects of CBX on DC vaccination are specific to the inhibition of 11bHSD1 in CD8a…”
Section: Discussionmentioning
confidence: 99%